2015
DOI: 10.1097/htr.0000000000000156
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Sports- and Recreation-Related Traumatic Brain Injuries Treated in US Emergency Departments

Abstract: Importance: Sports- and recreation-related traumatic brain injuries (SRR-TBIs) are a growing public health problem affecting persons of all ages in the United States. Objective: To describe the trends of SRR-TBIs treated in US emergency departments (EDs) from 2001 to 2012 and to identify which sports and recreational activities and demographic groups are at higher risk for these injuries. Design: Data on initial ED visits for an SRR-TBI from the National Electronic Injury Surveillance System-All Injury Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
170
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 270 publications
(190 citation statements)
references
References 46 publications
9
170
2
Order By: Relevance
“…Previous studies have described the incidence of sports-related TBI in adult ED populations. 10,23,46 Similarly, a large study in the Pediatric Emergency Care Applied Research Network, conducted between 2004 and 2006, recently reported that the overall incidence of sports-related TBI was 1%, with significant variation by type of sports. 20 However, the characteristics of inpatient hospital LOS, complications, discharge, and mortality rates in a large, nationally representative cohort have yet to be described.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have described the incidence of sports-related TBI in adult ED populations. 10,23,46 Similarly, a large study in the Pediatric Emergency Care Applied Research Network, conducted between 2004 and 2006, recently reported that the overall incidence of sports-related TBI was 1%, with significant variation by type of sports. 20 However, the characteristics of inpatient hospital LOS, complications, discharge, and mortality rates in a large, nationally representative cohort have yet to be described.…”
Section: Discussionmentioning
confidence: 99%
“…Sports and recreation-related concussions are serious injuries, with an estimated 325,000 children and teens treated in emergency departments for sports and recreation-related TBIs in 2012 (Coronado et al, 2015). That's just shy of 40 injuries every hour.…”
Section: Sports and Recreation-related Concussion Preventionmentioning
confidence: 99%
“…Previous studies have reported on the incidence of sports-related TBI in various ED populations. 10,17,39 However, the absence of inpatient and acute outcome data has precluded an analysis of hospital LOS, discharge disposition, and mortality rates after sports-related TBI. In the present analysis of an NTDB data set collected over a 10-year interval, we characterized the demographic profiles, hospital and ICU LOSs, medical complications, mortality rates, and discharge disposition across multiple broad categories of sports disciplines in adults admitted for sports-related TBI to Level I and Level II US trauma centers.…”
Section: Discussionmentioning
confidence: 99%